2022
DOI: 10.1038/s41598-021-04435-w
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of antimicrobial-resistant Escherichia coli in Sheltered dogs in the Kanto Region of Japan

Abstract: There is a lack of an established antimicrobial resistance (AMR) surveillance system in animal welfare centers. Therefore, the AMR prevalence in shelter dogs is rarely known. Herein, we conducted a survey in animal shelters in Chiba and Kanagawa prefectures, in the Kanto Region, Japan, to ascertain the AMR status of Escherichia coli  (E. coli) prevalent in shelter dogs. E. coli was detected in the fecal samples of all 61 and 77 shelter dogs tested in Chiba and Kanagawa, respectively. The AMR was tested against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Drug-resistant bacteria can be transmitted through close contact between pets and humans (such as petting, licking, or physical injuries) or through the home environment (such as contamination of food and furniture), posing a risk to children, the elderly, and pregnant or immunocompromised individuals [ 11 ]. Some high-income countries have investigated the antimicrobial resistance of E. coli carried by companion animals, such as the United Kingdom [ 12 ], the United States [ 13 ], Spain [ 14 ], Canada [ 15 ], Australia [ 16 ], Japan [ 17 ], and Thailand [ 18 ]. The prevalence of drug-resistant E. coli (86.64%) in this study was much higher than in most developed and even developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-resistant bacteria can be transmitted through close contact between pets and humans (such as petting, licking, or physical injuries) or through the home environment (such as contamination of food and furniture), posing a risk to children, the elderly, and pregnant or immunocompromised individuals [ 11 ]. Some high-income countries have investigated the antimicrobial resistance of E. coli carried by companion animals, such as the United Kingdom [ 12 ], the United States [ 13 ], Spain [ 14 ], Canada [ 15 ], Australia [ 16 ], Japan [ 17 ], and Thailand [ 18 ]. The prevalence of drug-resistant E. coli (86.64%) in this study was much higher than in most developed and even developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli is one of the most common microorganisms in the intestinal flora and is continuously exposed to antibiotic selection pressure. The authors found a prevalence of antibiotic-resistant E. coli exhibiting a variety of antibiotic resistance patterns equivalent to 86.64% (higher than results from other studies) [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Moreover, the study found that ESBL E. coli had a higher prevalence in cats than in dogs, which differs from the findings of other research [ 64 ].…”
Section: Antimicrobial Resistance (Amr) In Humans and In Animalsmentioning
confidence: 64%
“…Household pets live in close contact with humans and pose a substantial risk for transmission of illnesses and drug-resistant pathogens to susceptible owners, pet shop employees, veterinarians, as well as other animals ( Rees et al, 2021 ). Novel resistance determinants continue to emerge in zoonotic pathogens and commensal bacteria isolated from household pets, mostly dogs and cats ( Jackson et al, 2009 ; Leonard et al, 2011 ; Cummings et al, 2015 ; KuKanich and Lubbers, 2015 ; Zhang et al, 2016 ; Bourély et al, 2019 ; Li et al, 2021 ; Hata et al, 2022 ; Tóth et al, 2022 ). Dogs are increasingly recognized as a potential reservoir and a relevant transmission pathway of commensal and pathogenic bacteria or their resistance genes ( Harada et al, 2012 ; Damborg et al, 2016 ; Francois Watkins et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%